2020
DOI: 10.4314/njp.v47i4.7
|View full text |Cite
|
Sign up to set email alerts
|

Immunovirological treatment outcomes after 2 years of antiretroviral therapy in children living with the human immune deficiency virus in Lagos Nigeria

Abstract: Background/objective: The World Health Organization (WHO) recommends routine assessment of antiretroviral treatment outcomes to detect  treatment failure early and prevent the development of drug resistance. The aim of this study was to describe treatment outcomes of antiretroviral therapy (ART) over 2 years in children living with the human immune deficiency virus enrolled in the paediatric HIV clinic at the Lagos UniversityTeaching Hospital (LUTH).Materials and methods: This was a retrospective study of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Research in India showed the efficacy of using Tenofovir/Lamivudine/ Efavirenz as much as 98.7% and without high side effects (Sirohi et al, 2021). According to Nwaiwu et al (2019) the use of antiretroviral drugs for 2 years was not significantly associated with virological outcomes (viral load) and immunological failure based on absolute CD4 counts.…”
Section: Discussionmentioning
confidence: 99%
“…Research in India showed the efficacy of using Tenofovir/Lamivudine/ Efavirenz as much as 98.7% and without high side effects (Sirohi et al, 2021). According to Nwaiwu et al (2019) the use of antiretroviral drugs for 2 years was not significantly associated with virological outcomes (viral load) and immunological failure based on absolute CD4 counts.…”
Section: Discussionmentioning
confidence: 99%